Rapid solvo-microwave annealing for optimizing ordered nanostructures and crystallization of regioregular polythiophene-based block copolymers. Issue 36 (21st August 2019) - Han, Junghun; Kim, Jin-Seong; Shin, Jae Man; Yun, Hongseok; Kim, Youngkwon; Park, Hyeonjung; Kim, Bumjoon J.
Abstract : Solvo-microwave annealing is an effective method for producing thin films of polythiophene-based block copolymers with ordered structures and high crystallinity in a very short processing time (∼3 min). Abstract : Manipulation of crystalline structures of conjugated polymers (CPs) within nanostructured block copolymer (BCP) domains is crucial to enhance their electrical properties. However, this has been a challenge due to the intrinsic incompatibility between crystallization and phase-separation process of CP-based BCPs, which often causes break-out crystallization and results in disordered nanostructures and poor electrical properties. Herein, we demonstrate solvo-microwave annealing as an effective method for producing thin film structures of CP-based BCPs with well-ordered nanostructures and high crystallinity in a very short processing time (∼3 min). This approach is applied for poly(3-dodecylthiophene)- block -poly(lactic acid) (P3DDT- b -PLA) copolymers as a model system, where the PLA block offers the additional benefit of selective etchability to provide an on-chip etch mask for pattern transfer. The conventional thermal annealing process, even with a long annealing time (∼24 h), resulted in incompatibility between ordered nanostructures and the crystallization of the conjugated polymer. In contrast, the solvo-microwave annealing with a combination of heat and solvent vapor treatment was employed to grant enhanced chain mobility and solvent interaction with the π–π structure of the conjugated polymer. As a result, this process rapidly generated nanostructures with very few defects within 3 min and, at the same time, the highly crystalline intermolecular ordering of the P3DDT blocks occurred. Furthermore, we demonstrate the successful transfer of highly-ordered P3DDT structures after the removal of the PLA domain, which is important for potential applications in nanolithography and electronics.